An Approach for Innovation Outsourcing - Rehman, Shahwar (Cranfield University, 2013)
This study concerns facilitating organisational capability for outsourcing innovation, enabling firms to take advantage of its many benefits, (e.g., reduced costs, increased flexibility, access to better expertise and increased business focus), whilst mitigating its risks. Its purpose is to develop a generic holistic model to aid firms successfully outsource innovation. The model is developed in two stages using a qualitative theory building research design. The initial stage develops a preliminary model which is subsequently validated and refined during the second stage. Guided by the research aim, template analysis is used to inductively form an innovation outsourcing template from a literature data set assessed for its suitability. The template is interpreted as an innovation outsourcing archetype to produce a framework. This is explored, with the aid of influence diagrams, to make explicit the associations between innovation outsourcing capabilities, process and performance. The outcome is a set of propositions which constitute a preliminary innovation outsourcing model. The propositions which form the preliminary model are deductively explored to identify whether they also exist in a different data set. A methodically designed semi-structured interview survey is executed with the aid of a rich picture survey instrument to gather data for this purpose. The data is analysed through pattern matching and explanation building to explore the correlations which constitute the model. Where they correlate as predicted, propositions are confirmed. Where they do not, an explanation is sought and tested. The outcome is a validated innovation outsourcing model. The contribution to knowledge is an innovation outsourcing model which aids the realisation of performance. The model achieves this through a three-stage process which enables the alignment of capability to outsourced innovation activity, and makes actual performance outcomes, rather than expected benefits, the focus of innovation outsourcing aims.